2013
DOI: 10.1007/s00384-013-1655-3
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal gastrointestinal stromal tumors: a retrospective multicenter analysis of 15 cases emphasizing their high local recurrence rate and the need for standardized therapeutic approach

Abstract: Our results confirm the high local recurrence rate of anorectal GISTs (50%) which correlates with the common practice of suboptimal oncological primary tumor resection (Rx or R1 = 7/13). This uncommon subset of GISTs needs more standardized oncological surgical approach to minimize the propensity for local disease recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In patients undergoing local excision in the absence of perioperative imatinib treatment, high local recurrence rates have been reported compared to radical resection 18,24,25 . However, our data suggest this does not hold true in the modern era.…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing local excision in the absence of perioperative imatinib treatment, high local recurrence rates have been reported compared to radical resection 18,24,25 . However, our data suggest this does not hold true in the modern era.…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete resection, particularly in the area of the rectum, is also associated with a higher risk of recurrence. 120 As a group, PDGFRA-mutant GISTs appear to be less aggressive than KIT-mutant GISTs, 49 yet PDGFRA-mutant tumors can still progress and kill patients. These tumors are assessed using the same criteria as other GISTs.…”
Section: Assessing Gist Prognosismentioning
confidence: 99%
“…There are a few studies that have shown that the use of IM adjuvant therapy and subsequent local resection is better than, or at least not inferior to, LAR or APR for anorectal GISTs (9,10,11). The present study reports the cases of two rectal GISTs that were treated by IM adjuvant therapy and subsequent transsacral local resections.…”
Section: Discussionmentioning
confidence: 99%